"The mines make us poor": Large-scale mining in Burkina Faso - Franza Drechsel; Bettina Engels; Mirka Schäfer (Berlin, 2019)
GLOCON's new Country Report looks at the impact of industrial mining in Burkina Faso on the local rural population and presents the view of residents close to six industrial mines. Surveys in the affected villages show that - in contrast to the promises of mining companies and the government - the opening of the mines has not improved the living conditions. On the contrary, respondents report the loss of their livelihoods and damage to their health, as well as experienced disrespect by the mine operators. Those affected protest in various ways and demand compensation payments, the creation of jobs and income generating opportunities, as well as investment in local infrastructure. This report is available in English and French. – – Der neue Country Report von GLOCON beschäftigt sich mit den Auswirkungen des industriellen Bergbaus in Burkina Faso auf die lokale Bevölkerung und stellt den Blick von Anwohner*innen von sechs industriellen Minen vor. Befragungen in den betroffenen Dörfern zeigen, dass sich - entgegen der Versprechungen von Unternehmen und der Regierung - die Lebensbedingungen durch die Eröffnung der Minen nicht verbessert haben. Im Gegenteil: Die Befragten berichten vom Verlust ihrer Existenzgrundlagen und gesundheitlichen Schäden sowie von Respektlosigkeit, die sie seitens der Minenbetreiber erfahren. Die Betroffenen protestieren auf vielfältige Weise und fordern Entschädigung durch Kompensationszahlungen, die Schaffung von Arbeitsplätzen und Einkommensmöglichkeiten sowie Investitionen in die lokale Infrastruktur. Es gibt Versionen auf Englisch und Französisch.
urn:nbn:de:kobv:188-refubium-25016-4
Keywords: 330; Burkina Faso; industrial mining; protest